El impacto de los factores psico-sociales en el rendimiento escolar de niños y niñas de cuarto año de la escuela de educación básica España del cantón Puebloviejo - Vaca Fajardo, Lourdes Kimberlin (2016)
The present research was carried out with the purpose of improving the school performance of the children of fourth year of the School of Basic Education Spain of Canton Puebloviejo. Through various types of research we have performed an analysis of the academic level of the students of the above mentioned school where we can verify that if there is a representative percentage of children with low school performance, product of several psychosocial factors and factors characteristic of children The same ones that we have diagnosed and defined in our investigation. The research line on which the research was based is that aimed at the prevention and treatment of low academic performance, since this aspect is very important for the integral development of the individual. That is why as a source of help we have made the design of a practical guide for the teacher in which certain parameters are taught diagnosis and initial management of various factors that cause low academic performance of the student, so we can contribute to improve learning And thus improve the way of life that families lead.